TANGGUNG JAWAB SEWA MENYEWA RUMAH KONTRAKAN - Paritra Naya Pratama, I Putu; Sukranatha, Anak Agung Ketut (Kertha Semaya : Journal Ilmu Hukum, 2015)
The more rapid development of today's population is increasing also problems thatarise in people's lives, both from private self to a place where people lived, one of theproblems that occur in particular in the area is great is the issue of housing andsettlements. Because the density of the population who come, and the land is narrowand therefore many of which utilize their land to be used as a rented house that can berented as a residence for migrants who do not have a place to stay. The purpose of thispaper is to determine the responsibility of the lease if the tenant rented house in defaultor is negligent in this arrangement.In writing this paper, the type used normative research which refers to the books,as well as existing data. Legal responsibilities of stakeholders in the implementation ofthe rented house lease agreement can be seen in the rights and obligations of theparties, both the lessor and the tenant house. If the tenant does not do what his dutythen the lessor can sue to require the implementation of the agreement, or restitution orboth that can be requested along with the implementation of compensation
Keywords: Responsibility, Agreement, Rent, House